Investigation on fractal characteristics of salt rock under different tensile conditions. Issue 5 (September 2019) - Zhang, Qiangxing; Liu, Jianfeng; Huining, XU; Zeng, Yin; Wang, Chunping; Wang, Lu
Abstract: In order to study the characteristics of fractal dimension of salt rock and the change of its physical properties under different tensile conditions, the experiment of indoor indirect tensile, direct stretching, three-point bending and tensile pressure alternately was carried out on the pure salt rock, and the whole process was monitored by acoustic emission test system and the fracture scanning was performed after the test. The results showed that: (1) the fractal characteristics of the rock fracture roughness under different tensile conditions are related to the mechanical behavior. The higher the tensile strength, the smaller the fractal dimension of the cross section, and the smaller the roughness of the section. (2) under the four tensile conditions, the fractal dimension of the acoustic emission of salt rock shows a dimension reduction with the increase of stress and the release of energy, and the dimension reduction process is related to the mechanical characteristics of salt rock. Under the alternating stress path, the fractal feature of the acoustic emission location point of the salt rock appears more late, and the fractal dimension of the peak time is smaller than that under the direct tensile loading and unloading stress path, indicating that under the alternating stress path of tension and pressure, the internal damage of the salt rock is more aggregated; (3) the fractal dimension of the roughness and the fractal dimension of the roughness under the same tension condition. The results of acoustic emission fractal dimension calculation are highly similar.